Sosialisasi Kesadaran Diri Akan Bentuk Kekerasan Dan Pelecehan Seksual Bagi Anak Di Desa Paya Rengas Kecamatan Hinai Kabupaten Langkat - Saleh, Muhammad; Zaifatur Ridha; M. Junaidi; Intan Adila (peduli riset dan pengabdian masyarakat, 2025)
Violence and sexual harassment against children remain serious issues in various regions, including Paya Rengas Village, Hinai District, Langkat Regency. This socialization program was carried out by KKN (Student Community Service) group 07 to raise awareness among elementary school children about the forms of violence and sexual harassment, as well as preventive measures. The activity involved educational experts as speakers and was conducted at the village office hall using interactive lectures, simulations, and open discussions. The results showed an 85% increase in participants’ understanding of violence and preventive actions. Additionally, around 78% of children stated that they felt more confident in reporting cases of violence to teachers or parents. As a follow-up, the Office of Women’s Empowerment and Child Protection (PPA) of Langkat Regency plans to establish a Community-Based Integrated Child Protection (PATBM) program in Paya Rengas Village to create a more effective and sustainabl child protection system. The success of this program demonstrates that education and multi-stakeholder involvement are crucial in reducing child violence rates.